2017
DOI: 10.1080/10520295.2017.1278792
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced SOCS3 in osteoarthiritis may limit both proliferation and inflammation

Abstract: Osteoarthritis (OA) is a degenerative joint disease that is characterized by localized inflammatory and secondary proliferative changes. Suppressor of cytokine signaling 3 (SOCS3) is elevated during OA development. We investigated the effects of this protein on human chondrocyte survival in OA and the inflammatory response together with the mechanisms of these effects. Small interfering RNA (siRNA) was used to knock down the expression of SOCS3 in interleukin(IL)-1β-induced primary human osteoarthritic chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The nuclear factor-kappa B (NF-κB) transcription factor plays a central role in the pathogenesis of osteoarthritis [88]. It is triggered by proinflammatory cytokines and ECM degradation products [89].…”
Section: The Role Of Signaling Pathways and Other Inflammatory Componmentioning
confidence: 99%
“…The nuclear factor-kappa B (NF-κB) transcription factor plays a central role in the pathogenesis of osteoarthritis [88]. It is triggered by proinflammatory cytokines and ECM degradation products [89].…”
Section: The Role Of Signaling Pathways and Other Inflammatory Componmentioning
confidence: 99%
“…SOCS3 protein is commonly known to serve as a negative regulator of STAT3, which is the key physiological regulator in immune homeostasis and diseases pathogenesis [ 89 91 ]. SOCS3 has been shown to be induced by a wide variety of the cytokines and growth factors, such as IL-1β, 2, 4 and M-CSF [ 92 , 93 ]. Unlike its closest homologue, SOCS-3 molecules differ greatly in their mechanism of function of SOCS-1.…”
Section: Socs Proteins Family and Macrophage Polarizationmentioning
confidence: 99%
“…A previous study determined the prominent role of SOCS-3 in herniated lumbar disc degeneration by inhibiting the JAK/STAT3 signaling pathway (14). SOCS-3 also exhibits anti-inflammatory and anti-proliferation effects in osteoarthritis by downregulating levels of nuclear factor-κB and cyclooxygenase 2 (15). Dai et al (32) demonstrated that the upregulation of SOCS-3 expression results in reduced TNF-α levels and the regulation of Kallikrein-binding protein.…”
Section: Discussionmentioning
confidence: 99%